CDK4/6 inhibitors versus PI3K/AKT/mTOR inhibitors in women with hormone receptor-positive, HER2-negative metastatic breast cancer: An updated systematic review and network meta-analysis of 28 randomized controlled trials - Xu, Hangcheng; Wang, Yan; Han, Yiqun; Wu, Yun; Wang, Jiayu; Xu, Binghe (Frontiers in Oncology, 2022)
Background Updated evidence was required to compare the efficacy and safety of cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitors and phosphatidylinositol 3-kinase (PI3K) / protein kinase B (AKT) / mammalian target of rapamycin (mTOR) inhibitors for patients with HR-positive and HER2-negative metastatic breast cancer. Methods A systematic review and network meta-analysis was conducted utilizing data from randomized controlled trials (RCTs) which contained interventions of CDK4/6 inhibitors or PI3K/AKT/mTOR inhibitors. Progression-free survival (PFS), overall survival (OS), and treatment-related adverse events (TRAEs) were primary outcomes of interest. Pooled hazard ratios (HRs) and odds ratios (ORs) with 95% credible intervals (CrIs) were used to assess the survival outcomes and safety profiles, respectively. Results A total of 28 RCTs with 12,129 participants were included. Pooled analysis showed that CDK4/6 inhibitors significantly prolonged PFS than PI3K/AKT/mTOR inhibitors (HR 0.81; 95% CrI 0.69-0.94), while no significant differences were detected regarding OS. After balancing the treatment lines and metastatic sites, the superiority of CDK4/6 inhibitors only appeared in the visceral and non-visceral subgroups. Among CDK4/6 inhibitors, abemaciclib was significantly better than others in ≥3 grade neutropenia (OR 0.04; 95% CrI 0.01-0.15). The incidence of stomatitis and digestive disorders were different among diverse kinds of PI3K/AKT/mTOR inhibitors. Discrepancies appeared regarding TRAEs of hepatotoxicity, diarrhea, and hyperglycemia among different interventions. Conclusions CDK4/6 inhibitors showed better efficacy in PFS but the benefits disappeared when taking treatment line into consideration. Specific and discrepant safety profiles were found in two categories of agents.